EUROPEAN UNION ECONOMIC INTEGRATION AND DEVELOPMENT - Mihaela MUSAT (Challenges of the Knowledge Society, 2019)
At European level, the economic integration aims to achieve economic solidarity by forming a complex network of interdependent links between the economic agents of the participant countries. The viability of European economic integration depends primarily on the sharing of European democratic and cultural values by a state, and then on its economic capacity and performance. To contribute to the European Union development, the economic integration contributes by developing mutual exchanges and interdependences of national economies.